Hatching Time for the Eggs of Soft-shell Turtle, Kachuga dhongoka (Gray) at Various Temperatures - Yadava, M. R. (Indian Forester, 1980)
The eggs of soft-shell turtle,Kachuga dhongoka were collected directly from nesting sand bars of Saryu river in Ayodhya, Faizabad, U.P. and incubated in artificial conditions. It was observed that intermediate limit of temperature-25-27°C was appreciably most suited range for incubation while lower limit of temperature-20-22°C was insignificant range resulting in arresting or stopping the embryological development and upper limit of temperature 30-33°C was only significant for earliest hatchlings so far. Some time, the eggs or whole inest is infected at lower limit of temperature possibly due to slowest rate of metabolic activities in developing embryos while earliest hatchling were obtained at upper limit of temperature due to enhanced metabolic activities.